PENGEMBANGAN DESA WISATA DAN POTENSINYA DI KABUPATEN PANGANDARAN - Anang Muftiadi (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2017)
ABSTRACTThis research focus is on tourism activities development by utilizing the high intensity of Pangandaran Beach tourism. This research aim is to build the concept of village tourism which is comprehensively based on Community Based Tourism (CBT). The research method uses qualitative approach and contextual technique of regional development in Pangandaran Regency with the following stages (1) collecting secondary and primary data through field review (2) understanding of regional economic context (3) tourism potential analysis (4) conceptualization of tourism village development. The results showed that the development of tourist villages in Pangandaran Regency is an important step to diversify tourist destinations. The tourism village should have specific tourism objects (e.g: caves, rivers, lakes, plantations and typical rural nature, beaches etc.) and be associated with existing Pangandaran Beach tourism activities as the anchor. The government need to provides support for public infrastructure and facilities, builds a tourism forum network, provides stimulation and facilitation through a competition program to become a serious participation of the community.Keywords : Tourism destination diversification, villages tourism, community based tourism ABSTRAKPenelitian ini menjadi salah satu upaya untuk membangun konsep desa wisata di Kawasan Pangandaran yang komprehensif berbasis masyarakat dan berkelanjutan. Pendekatan pengembangan dilakukan dengan Community Based Tourism (CBT). Metode penelitian yang digunakan ialah pendekatan kualitatif dan teknik kontekstual pengembangan wilayah di Kabupaten Pangandaran dengan tahapan (1) mengumpulkan data sekunder dan primer melalui tinjauan lapangan (2) pemahaman konteks perekonomian daerah (3) analisis potensi wisata (4) konseptualisasi pengembangan desa wisata. Hasil penelitian menunjukkan bahwa pengembangan desa wisata di Kabupaten Pangandaran ialah langkah penting untuk diversifikasi destinasi wisata. Desa wisata yang dikembangkan harus memiliki obyek wisata spesifik (misalnya goa, sungai, danau, perkebunan dan alam perdesaan yang khas, pantai dan lain sebagainya) serta dikaitkan dengan dengan kegiatan wisata yang sudah ada sebagai anchor terdekat, yaitu Pantai Pangandaran. Pemerintah memberikan dukungan prasarana dan sarana publik, membangun jejaring forum wisata dan memberikan stimulasi dan fasilitasi pengembangan melalui program kompetisi untuk menjadi kesungguhan partisipasi masyarakat.Kata kunci : Diversifikasi tujuan wisata, desa wisata, community based tourism.